Accelerated rehabilitation in treating neer type V distal clavicle fractures using anatomical locking plates with coracoclavicular ligament augmentation. Issue 1 (January 2023) - Zou, Min; Duan, Xin; Li, Mufan; Sun, Jiachen
Abstract: Background: There is still no gold standard treatment for Neer type V distal clavicle fractures. This study was designed to evaluate the therapeutic effects of accelerated rehabilitation in treating Neer type V fractures using anatomical locking plate (ALP) fixation with additional coracoclavicular (CC) ligament augmentation. Methods: In this retrospective study, patients who underwent ALP fixation with additional suture anchor fixation of acute Neer type V distal clavicle fracture from January 2016 to January 2021 were reviewed. Injury radiography and computed tomography (CT) were performed to determine the Neer classification. All patients performed standardized early rehabilitation exercises after surgery and were followed up for more than 12 months. The Constant–Murley score (CMS); the disabilities of the arm, shoulder, and hand (DASH) questionnaire; visual analog scale (VAS); and the percentage of modified CC distance (MCCD%) were evaluated at the last follow-up. Results: Thirty-two patients were included in this study. The mean follow-up time was 31.1 ± 10.4 months. All patients achieved bone union 6–8 weeks (7.2 ± 0.7 weeks) after surgery and were allowed to return to normal daily life. No surgery-related complications occurred in any case. The MCCD% value at the last follow-up (104.7% ± 8.5%) significantly decreased compared with preoperative MCCD% value (162.8% ± 7.2%) (p < 0.001), indicating that all patients achieved ideal fracture reduction. And all patients obtained satisfactory shoulder joint function with a mean CMS of 97.1 ± 2.6, a mean DASH score of 1.6 ± 1.3, and a mean VAS score of 0.4 ± 0.6. Conclusion: This study has demonstrated that ALP fixation with additional suture anchor fixation is a promising strategy for accelerated rehabilitation in treating patients with Neer type V fracture.